Sovereign external debt and private sector entry in international financial markets - Brzozowski, Michał; Siwińska-Gorzelak, Joanna (Economics and Business Review, 2018)
The aim of this paper is to shed light on the public and private sector interdependencies in the international financial market. Using annual data on sovereign and private sector external indebtedness for 95 emerging and developing countries in the 1970-2012 period it looks at the relationship between the level and structure of public external debt and the likelihood of private sector entry in international bond and loan markets. The private sector entry in the offshore loans and bonds markets is shown to be conditional on the amount of public sector external debt. The relationship is complex but in general the saturation of the financial market with external government liabilities renders the private sector entry into the bonds’ market more difficult.